2014
DOI: 10.1007/s00256-014-1820-y
|View full text |Cite
|
Sign up to set email alerts
|

Image guided radiofrequency thermo-ablation therapy of chondroblastomas: should it replace surgery?

Abstract: Radiofrequency ablation appears to be a safe and effective alternative to surgical treatment with a low risk of recurrence and complications for most chondroblastomas. RF ablation is probably superior to surgery when chondroblastomas are small (less than 2.5 cm) with an intact bony margin with subchondral bone and in areas of difficult surgical access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 15 publications
0
38
0
3
Order By: Relevance
“…However, they found radiographic severity and symptom levels as factors that predicted total joint arthroplasty. Because arthritis occurred in more than half of our patients with proximal femur lesions, one might consider alternative approaches such as radiofrequency ablation and grafting through a more limited approach [13,19]. Despite careful surgical dislocation with attention to preserving the epiphyseal vessels, the femoral head sphericity was not retained in many of our patients and that incongruence of the ball and socket resulted in symptomatic hips needing a second surgical procedure [2].…”
Section: Discussionmentioning
confidence: 93%
“…However, they found radiographic severity and symptom levels as factors that predicted total joint arthroplasty. Because arthritis occurred in more than half of our patients with proximal femur lesions, one might consider alternative approaches such as radiofrequency ablation and grafting through a more limited approach [13,19]. Despite careful surgical dislocation with attention to preserving the epiphyseal vessels, the femoral head sphericity was not retained in many of our patients and that incongruence of the ball and socket resulted in symptomatic hips needing a second surgical procedure [2].…”
Section: Discussionmentioning
confidence: 93%
“…There have been no reports of any complications following femoral head RFA in previous studies, although complications in larger case series of RFA in periarticular operations have been mentioned. Rybak et al 4 and Lalam et al 3 reported articular surface collapse with the two largest sized tumors in their series (2.5x2.0x2.1 cm and 4.6x4.8x1.8 cm). Recurrence following radiofrequency ablation was mentioned in 1 of 17 cases reported by Rybak et al 4 and in 1 of 3 cases of Rajalakshmi et al 9 Using an alternative method for larger lesions, Petsas et al 7 treated two femoral head chondroblastomas with a combination of curettage and RFA with multitine electrodes (average tumor size 2.7 cm).…”
Section: Discussionmentioning
confidence: 85%
“…Several case reports have demonstrated that RFA can be applied to the periarticular area, especially the femoral head, proximal humerus, femoral condyle and tibial plateau. [2][3][4]7,8 In difficult areas, such as the femoral head, several case reports and case series have shown that RFA has had excellent outcomes in terms of head preservation, no growth plate damage and no tumor recurrence ( Table 1). The decision to treat with RFA is based on skeletal maturity and size of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RFA and other ablation techniques have been used to treat a variety of bone and soft tissue lesions such as osteoid osteomas, chondroblastomas, metastases, phosphaturic mesenchymal tumour, chondromyxoid fibroma, intracortical chondromas, enchondromas, eosinophilic granuloma, epithelioid haemangioma and extra-abdominal desmoid/fibromatosis [53][54][55][56][57][58][59][60] ( Figure 14). Any type of normal or abnormal tissue can be destroyed by an increase of temperature .60°C.…”
Section: Tumour Ablationmentioning
confidence: 99%